Salinity pretreatment synergies heat shock toxicity in cyanobacterium Anabaena PCC7120 - Srivastava, Rupanshee; Kanda, Tripti; Yadav, Sadhana; Singh, Nidhi; Yadav, Shivam; Prajapati, Rajesh; Kesari, Vigya; Atri, Neelam (Frontiers in Microbiology, 2023)
This study was undertaken to bridge the knowledge gap pertaining to cyanobacteria’s response to pretreatment. The result elucidates the synergistic effect of pretreatment toxicity in cyanobacterium Anabaena PCC7120 on morphological and biochemical attributes. Chemical (salt) and physical (heat) stress pretreated cells exhibited significant and reproducible changes in terms of growth pattern, morphology, pigments, lipid peroxidation and antioxidant activity. Salinity pretreatment showed more than 5 fold decrease in phycocyanin content but increase in carotenoid, lipid peroxidation (MDA content) and antioxidant activity (SOD and CAT), 6 fold and 5 fold at 1h and 3rd day of treatment, respectively, giving the impression of stress induced free radicals which is scavenged by antioxidant when compared to heat shock pretreatment. Furthermore, quantitative analysis of transcript (qRT-PCR) for FeSOD and MnSOD displayed 3.6 and 1.8 fold increase in salt-pretreated (S-H) samples. The upregulation of transcript corresponding to salt pretreatment suggests toxic role of salinity in synergising the heat shock. However, heat pretreatment suggests a protective role in mitigating salt toxicity. It could be inferred that pretreatment enhanced the deleterious effect. However, it further showed that salinity (chemical stress) augment the damaging effect of heat shock (physical stress) more profoundly than physical stress on chemical stress possibly by modulating redox balance via activation of antioxidant responses. Our study reveals that upon pretreatment of heat the negative effect of salt can be mitigated in filamentous cyanobacteria thus providing a foundation for improved cyanobacterial tolerance to salt stress.